Pediatric cataract surgery with hydrophilic acrylic intraocular lens implantation in Nepalese children - Adhikari S (Dove Medical Press, 2017)
Srijana Adhikari, Ujjowala D Shrestha Department of Pediatric Ophthalmology and Strabismus, Tilganga Institute of Ophthalmology, Kathmandu, Nepal Purpose: To assess the outcome of cataract surgery with hydrophilic acrylic intraocular lens (IOL) implantation in children with congenital and developmental cataracts.Method: A retrospective review of medical records of children with congenital or developmental cataracts who underwent cataract surgery with hydrophilic IOL implantation, from January 2011 to December 2014 in a tertiary eye hospital in Nepal. Primary posterior capsulotomy, anterior vitrectomy, and IOL implantation was done in children 8 years or younger, while older children underwent only lens aspiration and IOL implantation.Results: A total of 178 eyes of 120 children underwent cataract surgery with primary IOL implantation. Mean age at the time of surgery was 6.9 years (range: 3 months to 15 years). Average follow-up time was 13.7 (±5.9) months. Associated ocular anomalies were present in 84 (47.1%) eyes. Postoperative complications were found in 33 eyes (18.13%) with inflammatory membrane being the most common (10.1%). Two eyes (1.1%) developed endophthalmitis. Second intervention was needed in 12 (6.5%) eyes. Preoperative vision of less than 6/60 was present in 105 eyes (57.69%). Final best corrected visual acuity of 6/12 or better was found in 81 (44.5%) eyes.Conclusion: Our study shows that hydrophilic IOL is suitable for use in children. Results of this study are comparable with other studies on pediatric cataract surgeries using hydrophobic acrylic intraocular lenses. Low cost hydrophilic lens implantation is an effective approach in managing pediatric cataract surgery in developing countries like Nepal. Keywords: pediatric, cataract, hydrophilic, lens, Nepal